To solve the given equation, you need to simplify the bracket first by multiplying everything by -7. Therefore, -7 (8 + n) = -56 -7n = -91. Then, collect like terms together to get -7n = -91 + 56 = -35. Divide both sides by -7 to get -7n/-7 = -35/-7, n = -35/-7 = 5.
1 year ago
Last edited at 7:56PM on 8/15/2012
Cancel the negatives on both sides (basically dividing by -1) then u have 7(8+n)=91 divide each side by seven u should have 8+n=13 subtract 8 from each side u should have n=5 you could've also divided by -7 first. there's different ways to do things so yeah. this is how it's look i u divide by -7 first. -7(8+n)=-91 divide by negative 7 8+n=13 then subtract 8, and n=5